Ethical Leadership In Islamic Perspective And Impact On Educational Decision-Making - Nur Efendi (International Journal of Education Management and Religion, 2024)
This study investigates ethical leadership from an Islamic perspective and its impact on educational decision-making at MAN 3 Tulungagung. The study aims to analyze how ethical leadership is practiced, how it influences decision-making processes, and how both elements interact within the institutional context. A qualitative case study design was employed to explore experiences of the principal, teachers, and administrative staff. Data were collected through semi-structured interviews, observations, and document analysis, followed by thematic analysis to identify patterns related to leadership values and decision-making practices. The findings reveal that ethical leadership grounded in Islamic values such as integrity, justice, responsibility, and trustworthiness shapes transparent, participatory, and accountable decision-making processes. Leadership practices encourage open communication, fairness, and consistency in policy implementation, which strengthen institutional trust and professional commitment among staff. Decision-making becomes more inclusive and value-oriented, reflecting alignment between organizational goals and ethical considerations. The study also shows a dynamic interaction in which ethical leadership guides decision-making, implementation provides feedback, and leadership practices are continuously refined. These findings emphasize the importance of ethical leadership in fostering responsible and sustainable decision-making in Islamic educational institutions.